José Romera Castillo, Francisco Gutiérrez Carbajo y Mario García-Page (eds.): Literatura y multimedia. Madrid: Visor Libros, 1997, 386 pp. - Piñol, María Cruz (Signa: Revista de la Asociación Española de Semiótica, 2022)
-